What genetic model organisms offer the study of behavior and neural circuits. (2nd April 2016) - White, Benjamin H.
Abstract: The past decade has witnessed the development of powerful, genetically encoded tools for manipulating and monitoring neuronal function in freely moving animals. These tools are most readily deployed in genetic model organisms and efforts to map the circuits that govern behavior have increasingly focused on worms, flies, zebrafish, and mice. The traditional virtues of these animals for genetic studies in terms of small size, short generation times, and ease of animal husbandry in a laboratory setting have facilitated rapid progress, and the neural basis of an increasing number of behaviors is being established at cellular resolution in each of these animals. The depth and breadth of this analysis should soon offer a significantly more comprehensive understanding of how the circuitry underlying behavior is organized in particular animals and promises to help answer long-standing questions that have waited for such a brain-wide perspective on nervous system function. The comprehensive understanding achieved in genetic model animals is thus likely to make them into paradigmatic examples that will serve as touchstones for comparisons to understand how behavior is organized in other animals, including ourselves.